2020
DOI: 10.1126/science.aay5663
|View full text |Cite
|
Sign up to set email alerts
|

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease

Abstract: Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in NCKAP1L, which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 43 publications
1
120
0
Order By: Relevance
“…Loss of Hem1 and thus WRC function has severe and complex organismic consequences in mice 13,50,65 (see also Figure 1E) and men, 50,66,67 resulting in autoinflammation. Inefficiently cleared pathogens and apoptotic or necrotic cell bodies constitute major sources of inflammation and autoantibodies.…”
Section: Articlementioning
confidence: 99%
“…Loss of Hem1 and thus WRC function has severe and complex organismic consequences in mice 13,50,65 (see also Figure 1E) and men, 50,66,67 resulting in autoinflammation. Inefficiently cleared pathogens and apoptotic or necrotic cell bodies constitute major sources of inflammation and autoantibodies.…”
Section: Articlementioning
confidence: 99%
“…Recently, an immune dysregulation disorders characterized by deficit of the hematopoietic-specific WAVE complex regulator HEM1, coded by the NCKAP1L gene, has been characterized (no. 16 in Table 1 and Figure 1) (88). Patients with HEM1 deficiency suffer from recurrent infections, asthma and lymphoproliferation.…”
Section: Branching Defectsmentioning
confidence: 99%
“…For example, these technologies provided the association of homozygous mutations in Nck-associated protein 1-like (NCKAP1L) also known as Hem-1, a component of actin cytoskeleton machinery, with immune dysregulation and lympoproliferation. Proteomic studies in this case revealed an unsuspected interaction between Hem-1 and mTOR pathway [81].…”
Section: Genetic Diagnosis and Functional Validation Of Novel Ieimentioning
confidence: 77%